Mesoporous microspheres of nickel-based layered hydroxides by aerosol-assisted self-assembly using crystalline nano-building blocks - Tarutani, Naoki (2019)
Structural control in micro- and nanometer scales is necessary to design highly functional materials. Crystalline mesoporous microspheres (MMSs) are expected to improve electrochemical, catalytic, and adsorption performances. In this study, we focused on the preparation of templated MMSs of nickel-based layered hydroxides by using pre-crystallized nano-building blocks (NBBs). Layered nickel hydroxide nanoparticles were prepared through an epoxide-mediated alkalinization process and used as NBBs to construct microspheres. The spherical particles in micrometer scale were synthesized by an aerosol-assisted assembly of the NBBs dispersed in a solvent, in the presence of supramolecular templates. It was found that controlling the crystallization as well as the surface philicity permits to yield the NBBs with an adequately small size and interparticle interactions that generate self-assembled MMSs akin to those obtained in NBB-based mesoporous thin films. The preparation technique demonstrated here is highly versatile; templated MMSs with various chemical compositions of nickel-based layered double hydroxides were successfully obtained.